Integrative Protein-Based Prognostic Model for Early Stage Endometrioid Endometrial Cancer - Yang, Ji-Yeon (Clin Cancer Res, 2015)
PURPOSE: Endometrioid endometrial carcinoma (EEC) is the major histological type of endometrial cancer, the most prevalent gynecologic malignancy in USA. EEC recurrence or metastasis is associated with a poor prognosis. Early-stage EEC is generally curable, but a subset has high risk of recurrence or metastasis. Prognosis estimation for early-stage EEC mainly relies on clinicopathological characteristics, but is unreliable. We aimed to identify patients with high-risk early-stage EEC who are most likely to benefit from more extensive surgery and adjuvant therapy by building a prognostic model that integrates clinical variables and protein markers. EXPERIMENTAL DESIGN: We employed two large, independent early-stage EEC datasets as training (n = 183) and validation cohorts (n = 333), and generated the levels of 186 proteins and phosphoproteins using reverse-phase protein arrays. By applying an initial filtering and the elastic net to the training samples, we developed a prognostic model for overall survival containing two clinical variables and 18 protein markers and optimized the risk group classification. RESULTS: Kaplan-Meier survival analyses in the validation cohort confirmed an improved discriminating power of our prognostic model for patients with early-stage EEC over key clinical variables (log-rank test p-value = 0.565 for disease stage, 0.567 for tumor grade, 1.3×10(−4) for the integrative model). Compared with clinical variables (stage, grade, and patient age), only the risk groups defined by the integrative model were consistently significant in both univariate and multivariate analyses across both cohorts. CONCLUSIONS: Our prognostic model is potentially of high clinical value for stratifying patients with early-stage EEC and improving their treatment strategies.